DO NOTHING, FORWARD CONTRACT, MONEY MARKET HEDGE, OR CALL OPTION HEDGE THE CASE OF PT. GARUDA INDONESIA, TBK. - Abdul Azis Safii (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This study investigates the foreign exchange risk management program of PT. Garuda Indonesia, Tbk, an industry leading airlines in Indonesia with over to 50 countries Airlines route. PT. Garuda Indonesia, Tbk is one of that companies which has long been concerned on how to mitigate its economic and transaction exposure. The purpose of this project is to help the company mitigate its risk exposure and find the best hedging technique or other mitigation strategy to minimize their risk. The result of the project is to determine the most favorable hedging policy and the best way to implement the financial instruments or products available in the market or simulated. It is expected that PT. Garuda Indonesia, Tbk would be able to quickly execute hedging techniques in order to prevent financial loss due to foreign exchange exposure.